Integration of volatile and non-volatile metabolites and the transcriptome reveals the formation mechanisms of differential aroma compounds between Pyrus communis and Pyrus pyrifolia cultivars - Wang, Jiao; Guo, Xianping; Wu, Zhongying; Wang, Dongsheng; Guo, Peng; Han, Yongping; Jiang, Hui; Lü, Zhenzhen (Frontiers in Plant Science, 2025)
IntroductionAroma compounds are important flavor components in pear fruit. Among cultivated pears, fruits from Pyrus communis (hereafter referred to as P. communis) cultivars are famous for their abundant aroma, while the fruits of most Pyrus pyrifolia (hereafter referred to as P. pyrifolia) cultivars lack aroma compounds. A comparative study on the formation of differential aroma compounds between the two species could provide a theoretical foundation for improving the aroma quality of P. pyrifolia cultivars. However, there is a lack of systematic research on this subject.MethodsAn analysis of volatile and non-volatile metabolites was combined with transcriptome analysis to explore the formation mechanism of differential aroma compounds between three P. communis and three P. pyrifolia cultivars.ResultsIn this study, a total of 510 volatile compounds were identified in the six cultivars. Of these, sixteen ester and alcohol compounds, including butyl acetate, hexyl acetate, ethyl-2-methylbutyrate, ethanol, butanol, propanol, and 2-methylbutanol, with higher contents in the P. communis cultivars than in the P. pyrifolia cultivars were identified as the primary differential aroma compounds. Among the possible synthesis pathways for these 16 aroma compounds, certain amino acid degradation processes, including isoleucine, valine, and alanine oxidation and threonine dehydration, were found to provide important intermediate substances for synthesis. Within the key enzyme genes in the synthesis pathway, several critical enzyme genes, including monoacylglycerol lipase (PcMAGL, pycom08g09340), threonine dehydrase (PcTD, pycom12g10020), and acyl CoA dehydrogenase (PcACD, pycom16g13880), might be important factors contributing to the disparity in aromatic compounds between P. communis and P. pyrifolia cultivars.DiscussionThe aforementioned results provide valuable information into the formation mechanisms of differential aroma compounds and offer novel target sites for enhancing pear aroma quality through gene editing.